Computer simulation of Fresnel diffraction from rectangular apertures and obstacles using the Fresnel integrals approach - Abedin, Kazi Monowar; Islam, M.R.; Haider, A F M Yusuf (© 2005 Elsevier Ltd., 2017)
This article was published in the Journal Optics and Laser Technology [ © 2005 Elsevier Ltd.] and the definite version is available at: 10.1016/j.optlastec.2005.08.011